Global Perspectives on Religious Tolerance Curriculum in Primary Schools: A Systematic Literature Review - Rahman, Khalid; Sodiq, Jafar; Pranoto, Sugiyo; Supriyanto, Rubi; Mardhiyah, Ainatul; Lestari, Puji; Gusra, Dedy (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3629, 2025)
Religious tolerance education in primary schools has become crucial in addressing the growing global religious diversity and concerns about intolerance from an early age. However, few systematic studies review cross-country approaches to curricula and educational practices. This study aims to analyse the role of family and school environments, explore curricula and learning strategies, and identify challenges and solutions in religious tolerance education at the primary level. A systematic review was conducted using the PRISMA approach with databases Scopus, Web of Science, and Taylor & Francis. Article selection followed inclusion criteria from 2014–2024, English-language, and focused on primary education. Quality assessment used MMAT 2018, and thematic analysis was performed with NVivo 14. From 147 articles, 39 studies from 17 countries were synthesised. This is the first multi-continental synthesis. Four main themes were identified: family role, school role, synergy between both, and inhibiting factors. Schools play a dominant role, but family-school synergy and the use of technology remain underexplored. This research contributes that religious tolerance education requires holistic, integrative, and contextual approaches at the primary level in various countries. Further research is important in underrepresented regions such as Africa and Latin America.